An Examination of the Critical Factors of Store Brand Purchase Intentions - Zhao, XiaoQian (2011)
Consumer behaviour is very complex interaction of affect, cognition, behaviour and environment activities, which deals with how and why individuals conduct the exchange events of products and service. Brand, as a signal of quality assurance and sometimes a symbol of identity, plays a significant role in consumer decision making process. Thus build up brand assets and improve brand equity is important in brand management. As a main source of consumer packaged goods, store brands should be attached more importance in retail industry. There are many researches study the rationale of private label strategies and framework of household store brand proneness, yet, little empirical research has examined brand equity factors to influence the selection of store brand. This article augments prior research about factors influencing store brand purchase intentions by adding brand equity factors into private brand proneness model. The aim of this paper is to explore how store brand trust and store brand affect influence individual‟s attitude and behaviour intentions towards the store brand. It also studies the impacts of perceived quality variation, package and price on store brand trust, and the effects of personal characteristics such as openness to new experience and price consciousness on store brand affect and purchase intention. Whether frequent price promotion affects consumer choice directly and harms the value of store brand will also be examined in the developed path model. A literature review of brand, brand equity, as well as the influential factor of store brand proneness is undertaken. This study is based on an empirical research of consumer perception towards a health and care store --- the Watsons. The survey is conducted in Kuala Lumpur, Malaysia. 100 data is collected and is examined with reliability test, factor analysis, and regression analysis. The findings suggest that product price, openness to new experience and consumer price consciousness have weak direct effect on store brand trust, brand affect, and purchase intention respectively. However, perceived quality variation and package have a much stronger effect on store brand trust, which in turn, together with brand affect and price promotion, explain more than 50 percent of consumer‟s choice of store brand products.